Inventory Planning for Formula & Enteral Food Supply at Hasan Sadikin Hospital - Ardani, Muhamad; Simatupang, Togar M (The Indonesian Journal of Business Administration, 2012)
Nutrition Installation is a unit in hospital that manage nutrition service effectively and efficiently with optimal quality, including procurement, management, and distribution of food, nutrition therapy and nutrition counseling, as well as education and training (Health Ministry of Republic Indonesia). In providing food services for hospital customers, Nutrition Installation experiencing an overstock and stock out problems in formula & enteral food at daily warehouses as Nutrition Installation’s main warehouses.This research will discuss the improvement of inventory planning in main items of formula & enteral food at Nutrition Installation’s daily warehouses. Up until now, inventory planning of formula & enteral food based solely on intuition. This has become main cause of overstock and stockout condition in formula & enteral food.Inventory management that proposed in this final project is fixed order quantity with safety stock using forecasted demand. Forecasted demand is obtained by comparing several methods of forecasting; and from these several methods, exponential smoothing is the best forecasting method because has smallest value of error compared to the other methods. Therefore exponential smoothing method is suitable method to forecast the demand from each items of formula & enteral food supply.The reasult of the research in this final project is a saving from inventory cost about 70,78% a year for Ensure, 48,56% a year for Vitaplus, 62,19% a year for Entrasol, 64,95% a year for Peptisol, 80,21% a year for Pan Enteral, 75,16% a year for Peptamen, 67,33% a year for Pediasure, and 66,14% a year for Anlene; which is 66,80% potential saving from total inventory cost of formula & enteral food supply in one year period.In order to implement inventory management based on inventory planning that appropriate with demand characteristic, there are several steps that will involve related division in Nutrition Installation. First, conducted forecasting training by using calculation technique and computerized calculation using Mocrosoft Excell program. The next step is testing the inventory planning by monitoring the demand’s trend for 2 months and continue evaluation from this test begins. Keywords: Formula & Enteral Food, Overstock, Stock out, Nutrition Installation, Demand, Forecasting, Fixed Order Quantity with Safety Stock